Using Tensiometers for Vegetable Irrigation Scheduling in Miami-Dade County - Kati W. Migliaccio; Teresa Olczyk; Yuncong Li; Rafael Muñoz-Carpena; Tina Dispenza (EDIS)
A tensiometer is a simple and relatively inexpensive tool that can be used to schedule irrigation in Miami-Dade County vegetable crops. Tensiometers continuously measure soil water potential or tension. If the tension in the soil is high, plants have to use more energy to extract soil water. If tension in the soil is low, then plants have lower energy requirements to extract soil water. This revised 6-page fact sheet was written by Kati W. Migliaccio, Teresa Olczyk, Yuncong Li, Rafael Muñoz-Carpena, and Tina Dispenza, and published by the UF Department of Agricultural and Biological Engineering, December 2012.